1994
DOI: 10.1007/bf02984088
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification in the elderly patient after coronary artery bypass grafting: The prognostic value of radionuclide cineangiography

Abstract: Assessment of left ventricular ejection fraction at rest is prognostically useful after CABG among elderly patients. The efficacy and timing of this approach should be confirmed in further investigations with larger and more varied patient subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The one study that did evaluate the late postoperative course of 41 patients ≥ 65 years old who had undergone ERC ≥ 1 month after CABG reported an average follow up among patients with event free survival of 8.8 years after index radionuclide assessment. 10 Of the patients, 13 died of unknown causes, five had nonfatal MIs, and five underwent late repeat CABG or percutaneous transluminal coronary angioplasty. The authors identified only LVEF at rest as being significantly predictive of survival (p<0.04).…”
Section: Resultsmentioning
confidence: 99%
“…The one study that did evaluate the late postoperative course of 41 patients ≥ 65 years old who had undergone ERC ≥ 1 month after CABG reported an average follow up among patients with event free survival of 8.8 years after index radionuclide assessment. 10 Of the patients, 13 died of unknown causes, five had nonfatal MIs, and five underwent late repeat CABG or percutaneous transluminal coronary angioplasty. The authors identified only LVEF at rest as being significantly predictive of survival (p<0.04).…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Further work demonstrated that synchronicity of LV contraction could be derived from RNV by Fourier analysis of pixel by pixel labeled RBC time-activity curves, assigning a phase to each pixel (percent of the R-R interval from 0°-360°) to identify time of maximum contraction.…”
mentioning
confidence: 99%
“…2,3 Clinical trials soon showed that noninvasively determined LVEF was a strong predictor of survival in a broad range of heart diseases. 4,5 Further work demonstrated that synchronicity of LV contraction could be derived from RNV by Fourier analysis of pixel by pixel labeled RBC time-activity curves, assigning a phase to each pixel (percent of the R-R interval from 0°-360°) to identify time of maximum contraction. 6 Synchronicity has important effects on LV performance: patients with inter-or intra-ventricular asynchrony have lower LVEF relative to normal control subjects.…”
mentioning
confidence: 99%